Newton : - Newton, Isaac (W.W. Norton, 1995)
Contains a comprehensive collection of the life and works of Sir Isaac Newton covering his thoughts on alchemy and theory of matter, theology, mathematics, and other achievements and includes introductory essay, textual annotation, and chronology.